Pretransplant active disease status and HLA class II mismatching are associated with increased incidence and severity of cytokine release syndrome after haploidentical transplantation with posttransplant cyclophosphamide. (8th November 2019) - Mariotti, Jacopo; Taurino, Daniela; Marino, Fabrizio; Bramanti, Stefania; Sarina, Barbara; Morabito, Lucio; De Philippis, Chiara; Di Vito, Clara; Mavilio, Domenico; Carlo‐Stella, Carmelo; Della Porta, Matteo; Santoro, Armando; et al.
Abstract: Cytokine release syndrome (CRS) represents a life‐threatening side effect after haploidentical stem cell transplantation (Haplo‐SCT) with posttransplant cyclophosphamide (PT‐Cy). Factors predictive of CRS development is still a matter of debate. We retrospectively analyzed 102 consecutive patients receiving a bone marrow (BM) (n = 42) or peripheral blood stem cells (PBSC) (n = 60) Haplo‐SCT with PT‐Cy. The two cohorts were similar in main patients' characteristics besides disease type ( P = .02). Cumulative incidence of grades 1, 2, and ≥3 CRS was 80%, 52%, and 15% at a median of 2, 4, and 7 days, respectively. Moderate/High‐grade fever (39°‐41°), grade 1 and grade ≥3 CRS occurred more frequently after PBSC relative to BM grafts (68% vs 33%, P = .0005; 87% vs 71%, P = .009; 20% vs 7%, P = .07). Only patients experiencing grade ≥3 CRS had a worse outcome in terms of 1‐year overall survival (OS) and nonrelapse mortality (NRM): 39% vs 80% ( P = .002) and 40% vs 8% ( P = .005), respectively. By univariate analysis the only factors associated with the increased risk of ≥3 CRS were pretransplant disease status (8% for complete remission, 11% for partial remission, and 38% for active disease, P = .002), HLA‐DRB1 mismatching (57% vs 14%, P = .007), and PBSC graft ( P = .07). By multivariable analysis, only pretransplant disease status (hazard ratio, HR: 6.84, P = .005) and HLA‐DRB1 mismatching (HR: 17.19, P = .003) remained independent predictors of grade ≥3 CRS. Only grade ≥3 CRS is clinically relevant for the final outcome of patients receiving Haplo‐SCT with PT‐Cy, is more frequent after a PBSC graft and is associated with pretransplant active disease and HLA‐DRB1 mismatching. Abstract : Severe cytokine release syndrome (CRS) may occur after T‐cell‐replete haploidentical stem cell transplantation and conditions nonrelapse mortality. Disease burden and HLA mismatch in the graft‐vs‐host‐disease direction are the main factors affecting the occurrence of severe CRS.